Measuring the impacts of internet banking to bank performance - Evidence from Vietnam - Van, Dinh (ĐHKT, 2016)
Internet banking is an innovative service in the banking industry. However, researching about the impact of internet banking to banks performance is rarely seen. In Vietnam, no research has been found recently by researchers. The main objective of this study is to evaluate the impact of internet banking to performance of banks in Vietnam in the period from 2009-2014.